2018
DOI: 10.1245/s10434-018-6480-z
|View full text |Cite
|
Sign up to set email alerts
|

Troponin I2 as a Specific Biomarker for Prediction of Peritoneal Metastasis in Gastric Cancer

Abstract: TNNI2 expression in gastric tissues may serve as a specific biomarker for prediction of peritoneal metastasis of gastric cancer and contribute to improvement of patient management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…We found that the high expression level of TNNI2 was associated with good prognosis, while the high expression level of TTN, ACTN3, TNNC2 and MYL3 indicated poor prognosis. In addition to TTN and MYL3, previous studies have shown that the expression levels of TNNI2, ACTN3 and TNNC2 were closely related to the development, occurrence, invasion, metastasis and prognosis of tumors [79][80][81], which supports our analytical ndings. We analyzed the diagnostic and prognostic value of the Hub genes in OS for the rst time, and thus this study may serve as a reference for future studies on OS diagnosis and prognostic biomarkers.…”
Section: Discussionsupporting
confidence: 91%
“…We found that the high expression level of TNNI2 was associated with good prognosis, while the high expression level of TTN, ACTN3, TNNC2 and MYL3 indicated poor prognosis. In addition to TTN and MYL3, previous studies have shown that the expression levels of TNNI2, ACTN3 and TNNC2 were closely related to the development, occurrence, invasion, metastasis and prognosis of tumors [79][80][81], which supports our analytical ndings. We analyzed the diagnostic and prognostic value of the Hub genes in OS for the rst time, and thus this study may serve as a reference for future studies on OS diagnosis and prognostic biomarkers.…”
Section: Discussionsupporting
confidence: 91%
“…The patterns of MAGEA6 expression were graded depending on the percentage of stained cells as follows: 0-10%: No staining; 10-40%: weak staining; or 40-100%: strong staining (19). To avoid subjectivity, the specimens were randomized and coded before analysis by two independent observers uninformed as to the status of the samples (20). Each observer evaluated all specimens at least twice to minimize variations (21).…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…In recent years, researches had undertaken efforts to develop several biomarkers in identifying GC patients with peritoneal metastasis ( 29 31 ). However, most of them mainly focus on the clinicopathological parameters and ignore the components of genetic characteristics, which also play a critical role in peritoneal metastasis ( 32 ).…”
Section: Discussionmentioning
confidence: 99%